The National Agency for Protected Sectors and Its Role in Safeguarding Cultural Heritage During Crises - Mustapha , Doudou; Khadidja, Nechar; Omar, ZAABA (Journal of Ecohumanism, 2025)
Through this article, we will address the concept of the protected sector in Algeria and explore the mandate of the National Agency for Protected Sectors and its crucial role in safeguarding cultural heritage within Algeria's protected sectors. We will then shed light on experiences in cultural heritage protection in some Arab countries, such as Egypt, Syria, and Sudan. Next, we will clarify the importance of cultural heritage for national and human identity, and the various challenges it faces in emergencies, such as natural disasters and armed conflicts. Through a historical review of international agreements and key events that have contributed to shaping cultural heritage protection, I will analyze the legislative frameworks and policies guiding the agency's work. Furthermore, I will present case studies illustrating the agency's interventions and the challenges it faces, including resource constraints and legal obstacles. Based on the concept of an Emergency Plan, we will review the main reasons that necessitate preparing such a plan for the purpose of crisis preparedness. In the conclusion of the article, we will propose the essential strategies for enhancing crisis preparedness, such as strengthening risk awareness and leveraging technological innovations. Finally, we will identify the current gaps in practices and policies, providing recommendations for future improvements, while emphasizing the necessity of sustainable international cooperation to protect cultural heritage from imminent risks.